Analysis of Hydrophobic Droplets Surface Characteristics and ContactAngle on Wood Coating (SMART : Jurnal Teknologi Informasi dan Komputer, 2026)
Background: Wood-based products are widely used for both indoor and outdoor applications due to their lightweight nature, high strength, affordability, and ease of processing. However, wood easily absorbs water and moisture through cell lumen capillary forces and cell wall micropores, compromising its moisture stability and limiting its potential as a sustainable material. Surface coating is commonly used to address this weakness, prompting this study to evaluate the hydrophobic (water-repellent) qualities of coating materials against water droplets. Method: An experimental laboratory approach was conducted to evaluate the hydrophobic characteristics of wood surfaces following coating applications. The assessment measured the water-repellent performance against water droplets across different coating material types and application thicknesses. Result: All evaluated coating materials successfully enhanced the hydrophobic characteristics of the wood surface. Furthermore, the resulting hydrophobicity was not significantly influenced by either the type or the thickness of the applied coating. Conclusion: Surface coatings effectively improve the water-repellent properties of wood regardless of coating type or thickness. Further research is recommended to investigate how wood hardness affects surface coating performance and its resulting hydrophobic properties.